Multi-proxy records of paleoclimatic changes in sediment core ST2 from the southern Zhejiang-Fujian muddy coastal area since 1650 yr BP. (15th April 2022) - Hu, Jianxiong; Loh, Pei Sun; Chang, Yuan-Pin; Yang, Chin-Wen
Abstract: Sediment core 'ST2' collected from southern Zhejiang-Fujian muddy coastal area (ZFMA) was analyzed for grain size, bulk elemental composition (TOC and TN), stable carbon isotopes (δ 13 C), and lignin-derived phenols. The C/N ratios (6.2–10.1) and δ 13 C values (−21.7‰ to −23.0‰) demonstrated the predominance of marine organic matter. This was supported by a three end-member mixing model generated based on N/C ratio, δ 13 C, and Ʌ (total lignin in mg/100 mg of TOC). The results showed that marine and soil-derived organic matter accounted for 68.0% and 29.7%, respectively, of the total organic matter. The syringyl/vanillyl (S/V; 0.32 to 1.07) and cinnamyl/vanillyl (C/V; 0.13 to 0.91) ratios, together with the estimated range of lignin phenol vegetation index (LPVI) from 22.39 to 1451.91, indicated the predominance of non-woody angiosperms. The high vanillic acid/vanillin and syringic acid/syringaldehyde ratios suggested that the sediments were degraded prior to deposition. Our results showed that the variation of soil-derived organic matter along the core was affected by the East Asian monsoons, suggesting an anti-phase relationship between East Asian Winter Monsoon and East Asian Summer Monsoon. On the other hand, the temperature variations affected the abundance and type of vegetation. In addition, the variation of soil-derived organic matter showed remarkable consistency with other climate factors, such as solar irradiance, El Niño Southern Oscillation, North Atlantic Oscillation and North Atlantic ice drift. Meanwhile, the coherency relationship between the soil-derived organic matter and paleotyphoon activity indicates a possible linkage with paleotyphoon activity. Thus, the southern ZFMA was affected by both regional and global climatic factors, as well as extreme events-typhoon activity. Highlights: ● East Asian monsoons controlled the variation of the soil-derived organic matter. ● The vegetation type and abundance in southern Zhejiang-Fujian mud area can reflect temperature changes during the last 1650 yrs BP. ● Paleoclimate in southern Zhejiang-Fujian mud area was controlled by both regional and global climatic factors, as well as typhoon activities.